EFL students’ perspectives on the employment of language learning strategies - Duong, Tham My; Nguyen, Hang T. T. (Universitas Ahmad Dahlan, 2021)
It is widely acknowledged that language learning strategies (LLSs) are beneficial to learners’ academic achievements, learner autonomy and motivation; however, it is indicated that Vietnamese students, particularly high school students have found it hard to employ LLSs. This paper aims at exploring language learning strategies used by high school students and underlying reasons at a high school located in Ho Chi Minh City. The study involved 238 EFL high school students in responding to a closed-ended questionnaire and twenty of them in answering the semi-structured interview questions. The quantitative data collected from the questionnaire were processed by SPSS version 25.0 in terms of descriptive statistics, and the qualitative data were analyzed by the content-based approach. The results of the study indicated the EFL high school students’ moderate use of LLSs. Remarkably, metacognitive strategies were the most commonly used category, compared to memory strategies – the least employed category. The findings may serve as a guideline for EFL teachers on facilitating high school students’ English language learning. It is also hoped that the results of this study may contribute to the literature about English language learning strategies in EFL contexts.